Pengaruh Sudut Geram dan Parameter Pemesinan Terhadap Keausan Tepi Pahat High Speed Steel (HSS) pada Proses Bubut Glass Fibre Reinforce Polymer (GFRP) - Muhammad Yusra Nusa; Firman Ridwan (Department of Mechanical Engineering, Universitas Andalas, 2018)
The high rate of tool wear is an obstacle in machining of GFRP material. This research was conducted to investigate turning behavior towards the occurrence of flank wear on HSS devices by varying machining parameters such as rake angle, spindle speed and feed rate. The GFRP of workpiece was made from resin as a matrix and the glass type Chopped Strand Mat as fiber. The rack angle of tool is varied to 5º, 10º, 15º, 20º. Taguchi method was used to analized data experiments using orthogonal array L8. The experimental data shows that the spindle speed is the most influential parameter on flank wear with a S/N ratio of 4.10, followed by the feed rate with a S/N ratio of 3.08. Increasing rake angle can reduce wear, the smallest wear value was obtained at an angle of 20º.